Influence of Coating Protocols on Alumina-Coated Cathode Material: Atomic Layer Deposition versus Wet-Chemical Coating. Issue 15 (6th November 2019) - Han, Binghong; Key, Baris; Lipton, Andrew S.; Vaughey, John T.; Hughes, Barbara; Trevey, James; Dogan, Fulya
Abstract : Surface alumina coating is an effective way to protect the cathode materials in lithium-ion batteries, particularly when operating under high voltages. However, the actual structures and functions of surface alumina coatings formed by different synthesis methods are still not clear. In this work, we systematically compared two different synthesis approaches, wet chemical (WC) coating and atomic layer deposition (ALD), for alumina coatings on LiNi0.5 Mn0.3 Co0.2 O2 (NMC532). Using nuclear magnetic resonance and electron microscope characterizations, we found that high-temperature annealing can significantly affect the atomic and chemical structures of alumina coating layers formed by WC method, leading to the formation of more α-LiAlO2 buffer layer attached closely to the cathode particles and the improvement of electrochemical performance. Such strong interaction between cathode materials and alumina coatings during annealing is related to the Li extraction during the solution-based coating procedures. On the other hand, ALD-coated samples are less influenced by the high-temperature annealing, showing good electrochemical performance both before and after the heat-treatment. This work proves that different coating protocols have critical influences on the atomic and chemical structures of surface alumina coatings as well as the electrochemical performance of the coated cathodes.